The New Brunswick COPD Health Information Platform - Ted McDonald (International Journal of Population Data Science, 2019)
Background Chronic Obstructive Pulmonary Disease (COPD) afflicts one in five New Brunswick (NB), Canada residents aged 65+. The NB Institute for Research, Data and Training (NB-IRDT) has undertaken a project to develop an integrated COPD health information platform (CHIP) to study COPD in the NB population.